2007
DOI: 10.1016/j.jcss.2006.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Specification and verification of data-driven Web applications

Abstract: We study data-driven Web applications provided by Web sites interacting with users or applications. The Web site can access an underlying database, as well as state information updated as the interaction progresses, and receives user input. The structure and contents of Web pages, as well as the actions to be taken, are determined dynamically by querying the underlying database as well as the state and inputs. The properties to be verified concern the sequences of events (inputs, states, and actions) resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 29 publications
3
103
0
Order By: Relevance
“…The computation on a single node of a network is formalized by means of relational transducers [Abiteboul et al 2000;Ameloot et al 2011;Deutsch et al 2009;Deutsch et al 2007;Deutsch et al 2006;Spielmann 2003]. A transducer schema Υ is a tuple Υ in , Υ out , Υ msg , Υ mem , Υ sys of database schemas, called respectively "input", "output", "message", "memory" and "system".…”
Section: Transducersmentioning
confidence: 99%
“…The computation on a single node of a network is formalized by means of relational transducers [Abiteboul et al 2000;Ameloot et al 2011;Deutsch et al 2009;Deutsch et al 2007;Deutsch et al 2006;Spielmann 2003]. A transducer schema Υ is a tuple Υ in , Υ out , Υ msg , Υ mem , Υ sys of database schemas, called respectively "input", "output", "message", "memory" and "system".…”
Section: Transducersmentioning
confidence: 99%
“…Properties to be verified are specified using extensions of the classical temporal logics LTL, CTL and CTL*, in which propositions are interpreted as existential FO formulas on the tuple artifact and the underlying database. This yields the logics LTL-FO, CTL-FO and CTL*-FO [17,11,20]. It can be shown that regularity of the linear or branching-time service views for a class of artifact systems, with effectively constructible specifications, implies decidability of LTL-FO, resp.…”
Section: Examplementioning
confidence: 99%
“…Deutsch, Sui and Vianu in [18] introduced an approach that models data-driven web applications. This approach used Abstract State Machine to model the transitions between pages, determined by the input provided to the application.…”
Section: Related Workmentioning
confidence: 99%